1986
DOI: 10.1016/0014-5793(86)80347-7
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of the α‐subunit of bovine adenylate cyclase‐inhibiting G‐protein deduced from the cDNA sequence

Abstract: The primary structure of the a-subunit of the adenylate cyclase-inhibiting G-protein (G,) has been deduced from the nucleotide sequence of cloned DNA complementary to the bovine cerebral mRNA encoding the polypeptide. A much higher degree of amino acid sequence homology is observed between the ix-subunits of G, and transducin (68%) than between those of G, and the adenylate cyclase-stimulating G-protein (G,) (43%) or between those of transucin and G, (42%

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0

Year Published

1987
1987
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(53 citation statements)
references
References 34 publications
3
50
0
Order By: Relevance
“…(ii) Using stringencies of hybridization identical to those used for in situ hybridizations, all of the probes identified mRNA species on Northern blots with the same size as previously reported using 196 long cloned probes [14][15][16][17][18]24,25,27,28]. We suggest that the additional, larger, mRNA species observed with the G, and G, probes may represent unprocessed RNA transcripts.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…(ii) Using stringencies of hybridization identical to those used for in situ hybridizations, all of the probes identified mRNA species on Northern blots with the same size as previously reported using 196 long cloned probes [14][15][16][17][18]24,25,27,28]. We suggest that the additional, larger, mRNA species observed with the G, and G, probes may represent unprocessed RNA transcripts.…”
Section: Discussionsupporting
confidence: 65%
“…We call the bovine (241 and human [28] Gi sequences Gil. These sequences, obtained from brain cDNA libraries, agree precisely with the chemically determined sequence of Gi from rat [ 131 and bovine [24] brain. We term the Gi cloned from rat C6 glioma [ 131, mouse macrophage [ 141 and human monocyte [25] libraries Gi2.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…The cr subunits of Gi serve as the substrate of pertussis toxin-(lAP-) catalyzed ADP-ribosylation in their trimeric forms, have been classified into three subtypes of Oti-1, O/i-2 and o'i-3 from analyses of molecular cloning of the genes [2] and cDNAs [3][4][5][6]. In regard to the cesubunits of Go, at least two types of the genes were informed from Northern blot analysis [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in molecular cloning of Ga cDNAs revealed that they are highly similar proteins (4). So far, four Gsa (5), three Gia (4,6,41), two Gta (7), and Goa (4) cDNAs were isolated and their sequences were determined (see also ref. 1).…”
mentioning
confidence: 99%